Reflexões sobre o processo minoritário: design de moda, arte e audiovisual - Zapata, Maximiliano Oscar (2020)
The year 2018 marks a political turning point in Brazil: the ultra-conservative candidate wins the presidential election and institutes a government program that is not favorable to minorities. It is known that one of the strategies adopted in the campaign was the use of fake news on social networks, especially through the Whatsapp platform. The main fake news was the so-called gay kit. This communicational device, originally a school booklet aimed at combating homophobia in public high school institutions, became an instrument of power for the homophobic discourse of the conservative bench. Due to the negative effects of such a false value-building process in relation to the LGBTQ + community, we chose to study and reflect on the micropolitical practices of the groups affected by the conservative policies being implemented by the current power regime. Then, within the horizon of Queer Philosophy and Philosophy of Immanence, as well as Communication and Culture, with the definition of analysis artifacts from the world of art, fashion design and audiovisual resources, we seek to reflect critically on the process of struggle and social resistance faced by minority groups. Thus, with the theme of minority processes and philosophy, the objective was to understand the processes of construction of cultural objects as devices and machines of war, facing a context that oppresses and tries to subject minority bodies, to an order of beliefs and behaviors conservative, based on heteronormative values of patriarchal tradition. As a theoretical and investigative reference we are guided mainly by the studies of Guattari, Deleuze, Rolnik and Butler. Our fundamental question is crossed by the notion of becoming-woman, where drag queens, trans and gay women are affected as a counterpoint of strength in relation to the masculinist model. Thus, we seek to develop a mapping of the processes of minorization through a look at art, fashion design, audiovisual, performance drag. This work seeks, through the cartographic method, to reflect on a minority process, bringing together concepts of philosophy, communication, aesthetics and culture, in order to highlight studies already carried out on queer philosophy and philosophy of immanence as a theoretical contribution to the studies of gender and philosophy.